Prototype of Automatic Transfer Switch (ATS) for Solar Power Plant Based on Arduino Uno - Muhammad Alfian Haris Prastya; Bambang Purwahyudi (Fakultas Teknik Universitas Bhayangkara, 2023)
Electrical energy plays an important role in supporting daily human activities. The need for electrical energy always increases according to population growth. However, the supply of electrical energy is not proportional to population growth. To meet the demand for electrical energy, it is necessary to develop and use alternative energy such as solar energy. In this paper, the prototype of Automatic Transfer Switch (ATS) for PLN and solar power plant (SPP) is carried out so that the supply of electrical energy to the load can be distributed continuously. ATS is electromechanical equipment that operates automatically to move the source of electrical energy from the main grid (PLN) network to SPP when the PLN network occur a faults or blackout. ATS will restore the source of electrical energy from PLN automatically when the supply of electrical energy from PLN has returned to normal condition. ATS components consist of voltage and current sensors, microcontroller and relay respectively. ATS use microcontroller Arduino Uno ATmega328 type to control the main switch (relay) automatically. The test results show that ATS succeeded in moving the source of electrical energy from PLN to SPP when there is a disturbance or blackout condition and ATS will returns the source of electrical energy to PLN when conditions back to normal.